Phagocytosis Effectivity Test of Phenylbutenoid Compounds Isolated from Bangle (Zingiber cassumunar Roxb.) Rhizome (Biodiversitas Journal of Biological Diversity, 2008)
This study was conducted to determine the immunostimulant activity of several phenylbutenoid derivatives isolated frombangle (Zingiber cassumunar Roxb) rhizome: [1] [(E)-4-(3’,4’-dimethoxyphenyl)but-3-en-1-ol], [2] [(E)-4-(2’,4’,5’ trimethoxyphenyl) but-3-en-1-ol] and [3] [(E)-4-(3’,4’,1-trimethoxyphenyl)but-3-en-1-ol]. Immunostimulant activity was done by stimulating macrophage cells of mouse peritoneum. The result showed that [(E)-4-(3’,4’-dimethoxyphenyl)but 3-en-1-ol] compound had highest immunostimulant activity (99.0%) compared to compound 2 (93.7%) and 3 (80.0%).Key words: Zingiber cassumunar Roxb, immunostimulant, phenylbutenoid derivative, [(E)-4-(3’,4’-dimethoxyphenyl)but-3-en-1-ol], [(E)-4-(2’,4’,5’-trimethoxyphenyl)but-3-en-1-ol]and [(E)-4-(3’,4’,1-trimethoxy phenyl)but-3-en-1-ol